Model Pembelajaran Kooperatif dengan Presentasi Dapat Meningkatkan Kemampuan Belajar Administrasi Perkantoran (Menguraikan Karakteristik Administrasi Perkantoran) - Neneng Zuariah (Fakultas Ekonomi Universitas Negeri Jakarta, 2016)
ABSTRACT This study aims to determine efekifitas use cooperative learning model presentation can improve learning outcomes. Introduction to Office Administration, with the material characteristics Elaborating on the class X of Office Administration in SMK Negeri AP 1 SMK 48 2016. The study was conducted in August until October 2016, at SMK Negeri 48 Jakarta. Learning Model for this use is the type cooperative presentation, Class Action Research, which consists of two cycles, each cycle held three meetings and at the third meeting done Post Test. Research has reached the indicators that are expected in the second cycle, the number of students who get the value up to the limit completely or by 97, 46%, and the average value reached 80 to 79% Presentation Mastery students have achieved indicator is expected in this study. It can be said that student achievement has increased by using model Learning It can be concluded that by applying the procedure cooperative learning model proper presentation, can improve learning outcomes administrative offices with basic introductory material characteristics Outlines Administration in Class X AP 1 SMK Negeri 48 Jakarta in 2016. Keywords: Model Cooperative Learning, Learning Achievement, Characteristic Administration offices.